2013
DOI: 10.1017/s0033291713001335
|View full text |Cite
|
Sign up to set email alerts
|

Atypical interference effect of action observation in autism spectrum conditions

Abstract: BackgroundObserving incongruent actions interferes with ongoing action execution. This ‘interference effect’ is larger for observed biological actions than for non-biological actions. The current study used virtual reality to investigate the biological specificity of interference effects of action observation in autism spectrum conditions (ASC).MethodHigh-functioning adults with ASC and age- and IQ-matched healthy controls performed horizontal sinusoidal arm movements whilst observing arm movements conducted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 52 publications
1
44
1
Order By: Relevance
“…Additionally, our correlational findings suggest that the P3 is functionally related to the RT congruency effect. We could, however, not identify a relationship between the ERP congruency effects and non-clinical autistic traits (Bird et al, 2007;Cook et al, 2014;Gowen et al, 2008;Spengler et al, 2010). Overall, our study implies the existence of functionally distinct effects of perception on action, action on perception, and high-level selfother distinction within the imitation inhibition task.…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…Additionally, our correlational findings suggest that the P3 is functionally related to the RT congruency effect. We could, however, not identify a relationship between the ERP congruency effects and non-clinical autistic traits (Bird et al, 2007;Cook et al, 2014;Gowen et al, 2008;Spengler et al, 2010). Overall, our study implies the existence of functionally distinct effects of perception on action, action on perception, and high-level selfother distinction within the imitation inhibition task.…”
Section: Resultscontrasting
confidence: 73%
“…Moreover, the strength of motor interference effect was often noted as crucial to understand inadequate control over imitative behaviours in various patient groups (Cook, Barbalat, & Blakemore, 2012;Spengler et al, 2010), including autism spectrum disorder (ASD) (Bird, Leighton, Press, & Heyes, 2007;Cook, Swapp, Pan, Bianchi-Berthouze, & Blakemore, 2014;Gowen, Stanley, & Miall, 2008;Spengler et al, 2010). In the autism domain, it was suggested that individuals with ASD potentially lack high-level social-cognitive self-other distinction, which would lead to increased congruency effects within reaction times (hyperimitation effects; Bird et al, 2007;Sowden, Koehne, Catmur, Dziobek, & Bird, 2015;Spengler et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some of the studies reviewed above adhere neatly to the “like me” hypothesis by demonstrating evidence of behavioral overlap and increased engagement of the AON when participants observe familiar actions or interact with agents similar to themselves, while others do not. For example, other studies have demonstrated similar or greater AON engagement when participants observe very much unlike ‐me robotic actions compared to more familiar human actions, with similar findings for behavior engagement . Likewise, almost no correspondence with the “like me” hypothesis is found at the level of the PPN.…”
Section: Integrative Perspectivementioning
confidence: 87%
“…Automatic imitation studies seek to quantify the reflexive imitation of observed behavior, in this case, the interference of an observed robot's movements on the human perceiver's executed movements. Some evidence suggests that a biological motion profile of an observed agent impacts an observer's ongoing or subsequent movement more than a nonbiological motion profile, and that automatic imitation is greater for robotic movements with quasi‐biological motion . However, other studies call into question the necessity of biological motion of an observed action in order to interfere with the observer's motor performance.…”
Section: Impact Of Artificial Agent's Visual Featuresmentioning
confidence: 99%
See 1 more Smart Citation